The Effect of E-Wallet Use on Impulse Buying Behavior Students in Business Administration of Politeknik Negeri Kupang - Jessica Hermanus; Janri Delastriani Manafe (CV. Namora dan Riona Bersaudara, 2026)
The development of digital payment technology, particularly e-wallets, has influenced transaction patterns and consumer behavior, especially among students. This study aims to analyze the effect of e-wallet usage on impulse buying behavior among students of the Department of Business Administration at Politeknik Negeri Kupang. The research employs a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to 62 respondents selected using a simple random sampling technique. The data analysis used descriptive and inferential statistical methods, including classical assumption tests, simple linear regression, correlation analysis, and coefficient of determination. The results show that e-wallet usage has a positive and significant effect on students’ impulse buying behavior. This indicates that increased use of e-wallets tends to encourage spontaneous and unplanned purchases. The relationship between e-wallet usage and impulse buying is relatively strong, with e-wallets contributing significantly to explaining variations in impulse buying behavior, although other factors outside the research model also play a role. Theoretically, this study contributes to consumer behavior research related to digital payment systems. Practically, the findings emphasize the importance of digital financial literacy to promote responsible e-wallet usage among students.